Uses and Gratifications and social media: a cross-sectional quantitative questionnaire explaining the perceived role of organisational social media communication on customer loyalty in South Africa - Jacklin, Dylan (The IIE, 2018)
This research investigated the perceived role of organisational social media communication on customer loyalty in South Africa. The report argued, in line with the hypothesis, that organisational social media communication does have a role in establishing customer loyalty. The problem was that there was insufficient research on social media and customer loyalty in a South Africa context thus, more research was needed on the topic in South Africa. Uses and Gratifications Theory was used as a theoretical foundation to guide the study, applying two selected concepts, surveillance and personal relations. Data was collected using an online questionnaire of which 20 respondents, 10 males and 10 females were randomly selected. Data was compiled from the responses and analysed using descriptive statistics. This was done to quantitatively present a large number of responses within the context of the study. The findings were that organisational social media communication does have a role in establishing customer loyalty. This study has contributed additional findings in the fields of Media Studies and Customer Loyalty and provided organisations with information on how to better utilise social media to enhance customer loyalty.
Keywords: social media; consumer loyalty; surveillance; personal relations; Uses and Gratifications Theory